ChemInform Abstract: The Redox‐Mannich Reaction. Issue 48 (2nd December 2014) - Chen, Weijie; Seidel, Daniel
Abstract A new variant of the Mannich reaction that enables the facile preparation of ring‐substituted β‐amino ketones is developed.